Kompetensi Guru Keahlian Ganda Pasca Pelatihan On-In-On-In - Dian Julianto Wahyudi; Purnomo Purnomo; Yoto Yoto (Graduate School of Universitas Negeri Malang, 2019)
Abstract: The position of vocational productive teachers is very strategic in educating the life of the nation. In 2016, there were still a shortage of vocational productive teachers totaling 91,861 with details of 41,861 in State Vocational Schools and 50,000 in Private Vocational Schools. To fulfill teacher shortages with the addition of productive vocational teachers, the Dual Skills Program was performed. The Dual Skills Program is the addition of assignments and functions of teachers from normative and adaptive teachers plus the task of teaching productive expertise competencies, carried out for 12 months using the On-In-On-In learning model. This study answers how the expertise of multiple teacher competencies after On-In-On-In training in Jombang and Mojokerto. First, pedagogical mastery of dual expertise participants is good. Second, mastery of the skills of dual expertise teachers needs to be added. Third, mastery in making teaching aids for both products and services is quite good. Fourth, mastery in the learning method is quite good, the method used is the lecture method.Abstrak: Posisi guru produktif SMK sangat strategis dalam mencerdaskan kehidupan bangsa. Kondisi di tahun 2016 masih terdapat kekurangan guru produktif SMK sejumlah 91.861 dengan rincian 41.861 di SMK Negeri dan 50.000 di SMK Swasta. Upaya pemenuhan kekurangan guru tersebut dengan penambahan guru produktif SMK melalui Program Keahlian Ganda. Program keahlian ganda merupakan penambahan tugas dan fungsi guru dari guru normatif dan adaptif ditambah tugas mengajar kompetensi keahlian produktif, dilaksanakan selama 12 bulan menggunakan model pembelajaran On-In-On-In. Penelitian ini menjawab bagaimana kompetensi guru keahlian ganda pasca pelatihan On-In-On-In di kabupaten Jombang dan Mojokerto. Pertama, penguasaan pedagogik peserta keahlian ganda baik. Kedua, penguasaan keterampilan guru keahlian ganda perlu ditambah lagi. Ketiga, penguasaan dalam membuat alat peraga baik produk maupun jasa cukup baik. Keempat, penguasaan dalam metode pembelajaran cukup baik, metode yang digunakan adalah metode ceramah plus.